2019
DOI: 10.1186/s40795-019-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition education and cooking workshops for families of children with cancer: a feasibility study

Abstract: Background: Changes in food intake are common in children with cancer and are often caused by nausea and perturbations in sense of taste. The VIE (Valorization, Implication, Education) study proposes family-based nutrition and cooking education workshops during childhood cancer treatments. Process evaluation during implementation allows to assess if the intervention was delivered as planned and to determine its barriers and facilitators. The study objective was to describe the implementation process of a nutri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Further research should focus on how children and parents want to be supported on this topic. Interestingly, a recent feasibility study investigating nutrition education and cooking workshops for families of children with cancer, showed that the workshop "changes in taste during cancer therapy" was most useful to parents (18). This underscores how much difficulty parents and children have with taste changes and that providing ways to deal with these changes is very valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Further research should focus on how children and parents want to be supported on this topic. Interestingly, a recent feasibility study investigating nutrition education and cooking workshops for families of children with cancer, showed that the workshop "changes in taste during cancer therapy" was most useful to parents (18). This underscores how much difficulty parents and children have with taste changes and that providing ways to deal with these changes is very valuable.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients and families could face barriers to participating in in-person interventions. Beaulieu-Gagnon et al [ 41 ] identified common barriers faced by patients with childhood cancer in attending face-to-face nutrition classes. Notably, low attendance (17 participants over 1 year) resulted in the cancelation of 71% of their healthy cooking courses.…”
Section: Discussionmentioning
confidence: 99%
“…Children with cancer are more prone to malnutrition and excessive weight gain during treatment [23]. The use of corticosteroids may lead to a higher consumption of high-energy products [6,17].…”
Section: Adherence To Dietary Recommendations By Children and Adolescmentioning
confidence: 99%
“…Dzieci chore na nowotwory są bardziej narażone na niedożywienie i nadmierny przyrost masy ciała podczas leczenia [23]. Stosowanie kortykosteroidów może prowadzić do większego spożycia produktów wysokoenergetycznych [6,17].…”
Section: Dyskusjaunclassified